2012
DOI: 10.1038/labinvest.2011.165
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of novel germline c-kit gene mutation, KIT-Tyr553Cys, observed in a family with multiple gastrointestinal stromal tumors

Abstract: We found a novel type germline mutation at exon 11 of the c-kit gene, which results in a substitution of Tyr to Cys at codon 553 of the c-kit gene product (KIT-Tyr553Cys), in a 68-year-old female patient with multiple gastrointestinal stromal tumors (GISTs). In the present study, we carried out mutational analysis in her family members to determine the carriers and characterized the mutation by introducing the corresponding mutation (murine KIT-Tyr552Cys) into expression vector possessing murine c-kit cDNA. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Twenty families with familial GIST have arisen from exon 11 of KIT as described by Neuhann et al, 4 Nakai et al, 5 Adela et al, 7 and the cases presented here. KIT and PDGFRA are members of the family of class 3 tyrosine kinase receptors.…”
mentioning
confidence: 65%
“…Twenty families with familial GIST have arisen from exon 11 of KIT as described by Neuhann et al, 4 Nakai et al, 5 Adela et al, 7 and the cases presented here. KIT and PDGFRA are members of the family of class 3 tyrosine kinase receptors.…”
mentioning
confidence: 65%
“…As the present case showed a relatively weak response to conventional chemotherapy, we performed Sanger sequencing for the c‐kit gene and found a point mutation (Y553C, c.A1658G) in exon 11 (Figure f). A recent experimental study has revealed that KIT Y553C is a gain‐of‐function mutation, and that proliferation of murine lymphocytes expressing this mutant is effectively inhibited by imatinib and nilotinib, which are known ATP‐competitive tyrosine kinase inhibitors that can affect KIT with juxtamembrane domain mutation . Although these molecular drugs targeting intracranial germinomas have yet to be applied, it is speculated that the present case may have been sensitive to these tyrosine kinase inhibitors.…”
Section: Resultsmentioning
confidence: 87%
“…Out of the 35 familial GIST, including the present kindred, described so far, 22 carry mutations in exon 11 (encoding the juxtamembrane domain), seven in exon 13 (kinase I domain), four in exon 17 (kinase II domain), one single family, and one single patient in exons 8 and 9 (extracellular juxtamembrane domain), respectively …”
Section: Discussionmentioning
confidence: 87%
“…Familial GISTs, associated with germline c‐kit mutation, are a very rare inherited condition described so far in 34 different families . The KIT receptor is expressed on erythrocytes, melanocytes, germ cells, mast cells, and interstitial cells of Cajal (ICC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation